2019
DOI: 10.5935/0004-2749.20190007
|View full text |Cite
|
Sign up to set email alerts
|

Ocular abnormalities in morbid obesity

Abstract: Obesity is associated with eye diseases, but the underlying structural changes and pathogenic mechanisms have not been examined in detail. Here, we assessed the effects of morbid obesity on the morphometric indices of eye disease. Methods: Morbidly obese volunteers (n=101, body mass index [BMI] ≥40) and healthy individuals (n=95, BMI: 18.50-24.99) were examined by Goldman applanation tonometry, pachymetry, and spectral domain optical coherence tomography. Intraocular pressure, anterior chamber depth, axial len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…In the ophthalmological evaluation, significantly greater values of intraocular pressure were found in obese in both eyes, corroborating a finding already described in other studies in the literature [9] [10]. The increased intraocular pressure (IOP) in obese does not yet have a well-described pathophysiological mechanism, which may be related to hyperleptinemia present in obesity, which can trigger oxidative damage to the trabecular mesh, or else to the increase in orbital fat and blood viscosity, which increase episcleral venous pressure.…”
Section: Discussionsupporting
confidence: 90%
“…In the ophthalmological evaluation, significantly greater values of intraocular pressure were found in obese in both eyes, corroborating a finding already described in other studies in the literature [9] [10]. The increased intraocular pressure (IOP) in obese does not yet have a well-described pathophysiological mechanism, which may be related to hyperleptinemia present in obesity, which can trigger oxidative damage to the trabecular mesh, or else to the increase in orbital fat and blood viscosity, which increase episcleral venous pressure.…”
Section: Discussionsupporting
confidence: 90%
“…Of the 19 included studies in this meta-analysis, 5 measured macular thickness [ 9 , 20 , 26 28 ], 3 measured GC-IPL layer thickness [ 10 , 29 , 30 ], 5 measured RNFL thickness [ 12 , 27 , 28 , 31 , 32 ], and 7 studies measured peripapillary RNFL thickness [ 10 , 11 , 13 , 25 , 26 , 29 , 30 ], 5 measured cup to disc ratio [ 26 28 , 30 , 31 ], and 12 measured choroidal thickness [ 9 , 14 , 20 , 25 28 , 32 36 ]. All the studies reported their data as mean (SD), except one that reported some of the measurements in median (min-max) [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…All the studies were cross-sectional or case-control. Nine studies matched the obesity and control groups in terms of age [ 9 , 11 , 27 – 30 , 32 , 34 , 35 ], and 8 others matched their sex [ 9 , 27 – 30 , 32 , 34 , 35 ]. Nine studies analyzed a single eye of the subjects [ 9 , 14 , 20 , 28 30 , 32 34 ], 6 investigated both eyes [ 10 , 12 , 13 , 25 , 26 , 35 ], 2 studies used a mixed approach (both single eyes and both eyes) [ 11 , 31 ], and 2 others did not state it clearly [ 27 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, CCT did not differ between healthy and the morbid obese participants (p>0.05). The number of participants consisted of 101 morbid obese volunteers (body mass index [BMI] ≥40) and 95 healthy individuals (BMI: 18.50-24.99) (23). In our study, CCT values measured by ultrasound pachymetry tended to increase in obese children and significantly difference was found compared to the control group in Turkish cohort for children obesity.…”
Section: Discussionmentioning
confidence: 73%